Urban Water and Sanitation in Tanzania : Remaining Challenges to Providing Safe, Reliable, and Affordable Services for All - World Bank (World Bank, Washington, DC, 2018)
The purpose of the brief Urban Water and Sanitation in Tanzania: Remaining Challenges to Providing Safe, Reliable and Affordable Services for All is to outline the ways in which the Sustainable Development Goals (SDGs) framing of water and sanitation is helping us to understand not previously seen problems with urban services. For water services we see a reduction in the gap in access to improved and piped supply between rich and poor since 2005, with overall coverage currently standing at 85 in 2016. However, the low reliability of supply leads to a dependence on more expensive, informal service providers as a secondary source. This dependence can hit the poor hardest. In contrast, for sanitation we see a persistent and widening gap between rich and poor in improved access with a high proportion of shared facilities. Furthermore, as the SDG standards point out, lack of safe treatment and disposal of fecal matter can lead to a greater risk of contaminated water being ingested by the population, increasing the likelihood of waterborne disease such as cholera. Tanzania's cities, have experienced frequent outbreaks of cholera, with 4,985 cases reported in 2017.